Comparison of the effects of ozone therapy and photobiomodulation on sciatic nerve injury in rats - (:unkn) unknown (BAYRAKOL MEDICAL PUBLISHER, 2022)
Aim: Studies on drugs or alternative therapies are still the main treatment options for PNI. In this study, we aimed to research the effects of PBM and OT on nerve repair in a rat sciatic injury model. Material and Methods: 29 Wistar albino rats were divided into four groups: control (n = 2), sham (n = 9), OT (n = 9) and PBM (n = 9). After 30 days of surgery and treatments, tissue specimens and blood samples were taken for histological and biochemical processing. Histological evaluations were performed at light and electron microscopy levels. Myelin basic protein (MBP) and S100 from the rat serum were analysed also. Results: The OT and PBM groups had a significant increase in regeneration of the sciatic nerve in light microscopic evaluation. In the PBM and OT groups, Schwann cells (SC) around the axons and also axons with a thin myelin sheath were seen, regarded as signs of the myelination process in transmission electron microscopy (TEM) examinations. Discussion: OT and PBM both resulted in a good healing pattern for sciatic nerve injury in the rat model. Therefore, OT and PBM are considered to be simple and reliable alternative treatment methods for PNI.
Keywords: Ozone; Photobiomodulation; Sciatic Nerve; PAIN; MECHANISMS; LASER; S100; REGENERATION